Multimorbidity care model: Recommendations from the consensus meeting of the Joint Action on Chronic Diseases and Promoting Healthy Ageing across the Life Cycle (JA-CHRODIS). Issue 1 (January 2018) - Palmer, Katie; Marengoni, Alessandra; Forjaz, Maria João; Jureviciene, Elena; Laatikainen, Tiina; Mammarella, Federica; Muth, Christiane; Navickas, Rokas; Prados-Torres, Alexandra; Rijken, Mieke; Rothe, Ulrike; Souchet, Laurène; et al.
Highlights: Patients with multimorbidity have complex health needs. There is alack of evidence-based recommendations specific to multimorbidity patients. A consensus meeting was held to develop a framework multimorbidity patient care. The Multimorbidity care model includes sixteen components across five domains. These include: care delivery, decision and self-management support, technology, and community/social resources. Abstract: Patients with multimorbidity have complex health needs but, due to the current traditional disease-oriented approach, they face a highly fragmented form of care that leads to inefficient, ineffective, and possibly harmful clinical interventions. There is limited evidence on available integrated and multidimensional care pathways for multimorbid patients. An expert consensus meeting was held to develop a framework for care of multimorbid patients that can be applied across Europe, within a project funded by the European Union; the Joint Action on Chronic Diseases and Promoting Healthy Ageing across the Life Cycle (JA-CHRODIS). The experts included a diverse group representing care providers and patients, and included general practitioners, family medicine physicians, neurologists, geriatricians, internists, cardiologists, endocrinologists, diabetologists, epidemiologists, psychologists, and representatives from patient organizations. Sixteen components across five domains were identified (Delivery of Care; Decision Support; Self Management Support; Information Systems and Technology; and Social and Community Resources). The description and aim of each component are described in these guidelines, along with a summary of key characteristics and relevance to multimorbid patients. Due to the lack of evidence-based recommendations specific to multimorbid patients, this care model needs to be assessed and validated in different European settings to examine specifically how multimorbid patients will benefit from this care model, and whether certain components have more importance than others.